Typological Model of Textiles as a Kind of Applied Arts - Mitrofanova Natalia Yu. (Художественная культура, 2023)
The first theoretical interest in textiles as a type of applied arts arose in the 19th century. Since then, textiles have been the subject of research by individual specialists who have considered it from different points of view: as a technological product, a handicraft item, an artistic artefact, etc. However, a systematic, holistic view on textiles as a cultural phenomenon has not yet been formed. There is a lack of research that would include and take into account their natural essence, qualitative characteristics, range of purposes, and development of forms and types. The purpose of this study is to identify and substantiate the diversity of textiles in the process of their evolution. This goal can be achieved by using the system-categorical method of “a series of information criteria”. This method has been tested in various scientific fields, but has not yet been widely used in the field of artistic activity. The object of study is presented in it as a series of information criteria, each expressing one of its qualitative characteristics. The article presents a visual typologized model of the object through a constructive scheme composed of a series of information criteria, which consistently reflects the qualities of textiles arising from their purpose. As a result of the study, it has become possible to determine the logical sequence in which the types of textiles emerged, qualitatively describe and justify the existing forms, as well as research and develop new, previously unidentified forms and the corresponding options of their application.